Application of metal oxygen cluster modified ultrathin carbon nitride nanosheet in promotion of plant growth by artificial photosynthesis

By using ultra-thin carbon nitride nanosheets modified with metal oxygen clusters, the use of the solar spectrum by plants is expanded and the water oxidation performance of the photocatalyst is accelerated, the problem of low photosynthesis efficiency of plants is solved, and the growth of plants is significantly promoted, and nanosheets with stable structure and environmental protection are provided.

CN119896237AActive Publication Date: 2025-04-29HEILONGJIANG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510085227.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-29
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

In the prior art, the low utilization rate of plant solar spectrum leads to low photosynthesis efficiency. There has been no report on the use of ultra-thin carbon nitride modified with metal oxygen clusters to expand the utilization of plant solar spectrum and the transmission of long-lived photogenerated electrons generated by accelerating the water oxidation performance of photocatalysts to promote their growth.

Method used

Ultra-thin carbon nitride nanosheets modified with metal oxygen clusters expand the use of plants on the solar spectrum through their strong ultraviolet light absorption capacity, and improve the water oxidation performance of the photocatalyst through metal oxygen clusters, producing long-lived photogenerated electrons transferred to the chloroplasts of the plants, thereby promoting plant growth.

Benefits of technology

The photosynthesis efficiency of plants was significantly improved, with the fresh and dry weight of tobacco increasing by 21.9% and 17.8% respectively, and the fresh and dry weight of beets increasing by 25.1% and 57.8% respectively. At the same time, it provides nanosheets with stable structure, good optical properties and low toxicity, suitable for large-scale synthesis and meet the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119896237A_ABST
    Figure CN119896237A_ABST
Patent Text Reader

Abstract

The invention discloses application of a metal oxygen cluster modified ultrathin carbon nitride nanosheet in promoting plant growth through artificial photosynthesis, and relates to the technical field of nano agriculture. The invention aims to solve the problem of low photosynthesis efficiency caused by low utilization rate of the solar spectrum of the current plant. The method comprises the following steps: preparing metal oxygen cluster modified ultrathin carbon nitride nanosheets into a water dispersion liquid with a certain concentration, and spraying the dispersion liquid of the metal oxygen cluster modified ultrathin carbon nitride nanosheets onto leaf surfaces of plants, so that the growth promoting effect on the plants is better; the fresh weight and the dry weight of the plants are obviously improved. And the plant growth promoting effect of the photocatalyst is in positive correlation with the water oxidation performance of the photocatalyst. The metal oxygen cluster modified ultrathin carbon nitride nanosheet is good in stability, wide in source, good in biocompatibility and friendly to ecology and environment, meets the requirement of sustainable development, and can be widely applied to crop planting. The invention provides a novel method for improving the photosynthesis efficiency of plants and promoting the yield increase and income increase of crops.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-agriculture, and in particular to the application of an ultra-thin carbon nitride nanosheet modified by a metal oxygen cluster in promoting plant growth through artificial photosynthesis. Background Art

[0002] The shortage of fossil energy and the intensification of environmental pollution have increased people's desire for efficient use of solar energy. Natural photosynthesis is one of the most successful ways for nature to utilize solar energy. However, due to the low efficiency of plant conversion of light energy, the photosynthesis efficiency is low. Therefore, it is of great significance to develop green and feasible ways to improve the efficiency of plant photosynthesis and promote plant production and income.

[0003] The principle of photocatalysis technology (also known as artificial photosynthesis) is that semiconductors are excited by light to produce photogenerated electron-hole pairs, which migrate to the surface of the catalyst to trigger a series of redox reactions, such as H2O decomposition, CO2 reduction and N2 fixation. Therefore, artificial photosynthesis promotes natural photosynthesis, and is expected to improve the efficiency of natural photosynthesis and promote plant growth by expanding the spectral utilization range of natural photosynthesis and transferring long-lived photogenerated electrons generated by improving the water oxidation performance of photocatalysts to plant chloroplasts.

[0004] Carbon nitride (CN) is a widely used semiconductor photocatalyst. It is stable, widely available, and has good biocompatibility. It is eco-friendly and environmentally friendly, meets the requirements of sustainable development, and can be widely used in crop cultivation. There are reports that carbon nitride promotes plant photosynthesis through fluorescence conversion. However, there is still a problem of low spectral utilization leading to low photosynthesis efficiency. There are no reports on metal oxygen cluster-modified ultrathin carbon nitride expanding the utilization of plant solar spectrum and promoting its growth by accelerating the transfer of long-lived photogenerated electrons generated by the water oxidation performance of photocatalysts to plant chloroplasts. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of low photosynthesis efficiency caused by low utilization of the solar spectrum of plants, and to provide an application of ultrathin carbon nitride nanosheets modified by metal oxygen clusters in promoting plant growth through artificial photosynthesis.

[0006] Artificial photosynthesis of ultrathin carbon nitride nanosheets (M-COS-CN) modified by metal oxygen clusters is used to promote plant growth. Carbon nitride can expand the utilization of the solar spectrum by plants because of its strong ultraviolet light absorption ability. In addition, by improving the water oxidation performance of carbon nitride-based photocatalysts through metal oxygen clusters, long-lived photogenerated electrons will be generated, which are further transferred to the chloroplasts of plants, which will increase the electron transfer rate in the electron transfer chain and promote their growth. Therefore, the present invention uses a series of ultrathin carbon nitride nanosheets modified by metal oxygen clusters to promote plant growth, which has certain application prospects.

[0007] A metal oxygen cluster modified ultrathin carbon nitride nanosheet is used to promote plant growth, which specifically includes the following steps:

[0008] The metal oxygen cluster modified ultra-thin carbon nitride nanosheets are configured into a water dispersion of a certain concentration, and then the water dispersion of the metal oxygen cluster modified ultra-thin carbon nitride nanosheets is sprayed onto the leaves of the plants;

[0009] The metal oxide cluster modified ultrathin carbon nitride nanosheets are: manganese oxide cluster modified ultrathin carbon nitride nanosheets, ruthenium oxide cluster modified ultrathin carbon nitride nanosheets, manganese oxide cluster modified ultrathin boron doped carbon nitride nanosheets or ruthenium oxide cluster modified ultrathin boron doped carbon nitride nanosheets.

[0010] Beneficial effects of the present invention:

[0011] (1) Foliar spraying of photocatalysts greatly promoted plant growth. After treatment with ultrathin carbon nitride nanosheets modified with manganese oxide clusters, the fresh weight of tobacco increased by 21.9% and the dry weight increased by 17.8%. The fresh weight of sugar beets increased by 25.1% and the dry weight increased by 57.8%.

[0012] (2) The metal oxygen cluster-modified ultrathin carbon nitride nanosheets prepared by the present invention have the characteristics of stable structure, good optical properties, and low toxicity, especially strong absorption in the ultraviolet region of 300 to 400 nm, and good water oxidation performance;

[0013] (3) The preparation method of the metal oxygen cluster modified ultrathin carbon nitride nanosheets of the present invention is simple and suitable for large-scale synthesis;

[0014] (4) The metal oxygen cluster-modified ultrathin carbon nitride nanosheets of the present invention are ecologically and environmentally friendly due to their good stability, wide sources, and good biocompatibility, and meet the requirements of sustainable development, and can be widely used in crop planting. The present invention provides a new method for improving the efficiency of plant photosynthesis and promoting crop yield and income increase. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Structural characterization of the ultrathin carbon nitride nanosheet modified with ruthenium oxide clusters prepared in Example 1;

[0016] Figure 2 The morphology and thickness of the ultrathin carbon nitride nanosheet modified with ruthenium oxide clusters prepared in Example 1;

[0017] Figure 3 To investigate the effect of the ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters prepared in Example 1 on tobacco growth;

[0018] Figure 4 The effect of the ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters prepared in Example 1 at different concentrations on tobacco growth in Application Example 2;

[0019] Figure 5 Structural characterization of the ultrathin carbon nitride nanosheet modified with manganese oxide clusters prepared in Example 3;

[0020] Figure 6 The effect of the ultrathin carbon nitride nanosheets modified with manganese oxy-cluster prepared in Example 3 on tobacco growth in Application Example 4;

[0021] Figure 7 In Example 5, the ultrathin carbon nitride nanosheets modified with manganese oxide clusters prepared in Example 3 were used to investigate the effect on the growth of sugar beets. DETAILED DESCRIPTION

[0022] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0023] Specific implementation method 1: This implementation method is an application of ultra-thin carbon nitride nanosheets modified by metal oxygen clusters in promoting plant growth by artificial photosynthesis. The ultra-thin carbon nitride nanosheets modified by metal oxygen clusters in artificial photosynthesis are used to promote plant growth, specifically including the following steps:

[0024] The metal oxygen cluster modified ultra-thin carbon nitride nanosheets are configured into a water dispersion of a certain concentration, and then the water dispersion of the metal oxygen cluster modified ultra-thin carbon nitride nanosheets is sprayed onto the leaves of the plants;

[0025] The metal oxide cluster modified ultrathin carbon nitride nanosheets are: manganese oxide cluster modified ultrathin carbon nitride nanosheets, ruthenium oxide cluster modified ultrathin carbon nitride nanosheets, manganese oxide cluster modified ultrathin boron doped carbon nitride nanosheets or ruthenium oxide cluster modified ultrathin boron doped carbon nitride nanosheets.

[0026] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that: the process of configuring the ultra-thin carbon nitride nanosheets modified by metal oxygen clusters into a water dispersion of a certain concentration is as follows: adding the ultra-thin carbon nitride nanosheets modified by metal oxygen clusters to water, and then ultrasonicating for 10min to 60min at an ultrasonic power of 100W to obtain an aqueous dispersion of the ultra-thin carbon nitride nanosheets modified by metal oxygen clusters; the concentration of the aqueous dispersion of the ultra-thin carbon nitride modified by metal oxygen clusters is 50mg / L to 200mg / L. The other steps are the same as those of specific embodiment 1.

[0027] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the plant is tobacco, sugar beet, rice, corn or soybean. The other steps are the same as those of specific implementation method 1 or 2.

[0028] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the plants are cultivated in a soil culture mode. The other steps are the same as those of specific implementation methods 1 to 3.

[0029] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the method for preparing the ultra-thin carbon nitride modified with manganese oxide clusters is specifically completed according to the following steps:

[0030] 1. Preparation of ultrathin carbon nitride nanosheets and ultrathin boron-doped carbon nitride nanosheets:

[0031] The urea is placed in an alumina crucible and transferred to a muffle furnace for primary calcination, cooled naturally to room temperature, and then ground to obtain product I; the product I is placed in a semi-enclosed magnetic boat, and then placed in a muffle furnace for secondary calcination, cooled naturally to room temperature, and then ground to obtain product II; the product II is placed in a round-bottom flask, acidified after adding acid, cooled to room temperature, centrifuged, washed with water to neutrality, and dried to obtain ultra-thin carbon nitride nanosheets; the product I is mixed with sodium borohydride, ground for a period of time, and then placed in a vacuum tube furnace for calcination, and the product obtained after calcination is washed with water and dried to obtain ultra-thin boron-doped carbon nitride nanosheets;

[0032] 2. placing ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets and chitosan oligosaccharide in a beaker, adding a certain amount of deionized water to mix, and obtaining a mixture; after stirring the mixture for several hours, placing it in a polytetrafluoroethylene-lined high-pressure reactor for hydrothermal reaction, cooling it to room temperature, centrifuging, washing, and drying, and obtaining ultrathin carbon nitride nanosheets modified with chitosan oligosaccharide or ultrathin boron-doped carbon nitride nanosheets modified with chitosan oligosaccharide;

[0033] 3. Disperse the chitosan oligosaccharide-modified ultrathin carbon nitride nanosheets or chitosan oligosaccharide-modified ultrathin boron-doped carbon nitride nanosheets in deionized water, then add a metal source, stir for several hours, and then place in a polytetrafluoroethylene-lined autoclave for reaction, cool to room temperature, centrifuge, wash, and dry to obtain metal oxygen cluster-modified ultrathin carbon nitride nanosheets. The other steps are the same as those in the first to fourth embodiments.

[0034] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the process of the primary calcination described in step 1 is as follows: in air, the temperature is raised from room temperature to 400°C to 600°C at a heating rate of 0.1°C / min to 1°C / min, and then calcined at 400°C to 600°C for 2h to 4h; the process of the secondary calcination described in step 1 is as follows: in air, the temperature is raised from room temperature to 400°C to 600°C at a heating rate of 5°C / min to 10°C / min, and then calcined at 400°C to 600°C for 2h to 4h; the acid described in step 1 is 1mol / L to 5mol / L nitric acid; the temperature of the acidification treatment described in step 1 is 100°C to 120°C, and the time of the acidification treatment is 1h to 3h; the mass ratio of the product II described in step 1 to the volume ratio of the acid is (1g to 2g): (100mL to 200mL). The other steps are the same as specific embodiments 1 to 5.

[0035] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the mass ratio of product I to sodium borohydride in step 1 is (0.2-0.4):(0.1-0.3); in step 1, product I is mixed with sodium borohydride, ground for 2-5 minutes, and then placed in a vacuum tube furnace at a temperature of 450-550°C for calcination for 1-3 hours, and the calcined product is washed with water 3-5 times to obtain ultrathin boron-doped carbon nitride nanosheets. The other steps are the same as those in specific embodiments 1 to 6.

[0036] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: the mass ratio of chitosan oligosaccharide to ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets in the mixture described in step two is (1-5):100; the mass ratio of ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets in the mixture described in step two to the volume ratio of deionized water is (0.2g-0.3g):(20mL-30mL); the stirring time described in step two is 5h-8h. The other steps are the same as specific embodiments one to seven.

[0037] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that: the temperature of the hydrothermal reaction described in step 2 is 100℃~120℃, and the time of the hydrothermal reaction is 2h~4h; the centrifugal process described in step 2 is: centrifuge for 3min~5min at a centrifugal speed of 3000r / min~4000r / min, and then remove the supernatant to obtain a solid substance; the washing described in step 2 is: washing with deionized water 3 times~5 times; the drying temperature described in step 2 is 60℃~80℃, and the drying time is 10h~24h. The other steps are the same as specific embodiments 1 to 8.

[0038] Specific embodiment 10: The difference between this embodiment and specific embodiments 1 to 9 is that: the metal source described in step 3 is manganese nitrate or ruthenium chloride; the mass ratio of the metal element in the metal source described in step 3 to the ultra-thin carbon nitride nanosheet modified with chitosan oligosaccharide or the ultra-thin boron-doped carbon nitride nanosheet modified with chitosan oligosaccharide is (1 to 3): 100; the mass ratio of the ultra-thin carbon nitride nanosheet modified with chitosan oligosaccharide or the ultra-thin boron-doped carbon nitride nanosheet modified with chitosan oligosaccharide described in step 3 to the volume ratio of deionized water is (0.2g to 0.3g): (20mL to 30mL); the centrifugation process described in step 3 is: centrifugation at a centrifugal speed of 3000r / min to 4000r / min for 3min to 5min, and then removing the supernatant to obtain a solid substance; the washing described in step 3 is: washing with deionized water 3 to 5 times; the drying temperature described in step 3 is 60℃ to 80℃, and the drying time is 10h to 24h. The other steps are the same as specific embodiments 1 to 9.

[0039] The following examples are used to verify the beneficial effects of the present invention:

[0040] Example 1: A method for preparing ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters (Ru-COS-CN) is specifically completed by the following steps:

[0041] 1. Preparation of ultrathin carbon nitride nanosheets and ultrathin boron-doped carbon nitride nanosheets:

[0042] 35 g of urea was placed in an alumina crucible and transferred to a muffle furnace for primary calcination, cooled naturally to room temperature, and then ground to obtain product I; product I was placed in a semi-enclosed magnetic boat, and then placed in a muffle furnace for secondary calcination, cooled naturally to room temperature, and then ground to obtain product II; product II was placed in a round-bottom flask, added with acid, refluxed at 120° C. for 2 h, cooled to room temperature, centrifuged, and the collected solid matter was washed with deionized water until neutral, and then dried at 80° C. for 24 h to obtain ultrathin carbon nitride nanosheets (CN);

[0043] The process of the primary calcination in step 1 is as follows: in air, heating from room temperature to 550°C at a heating rate of 0.5°C / min, and then calcining at 550°C for 3h;

[0044] The secondary calcination process described in step 1 is as follows: in air, heating from room temperature to 500°C at a heating rate of 5°C / min, and then calcining at 500°C for 2h;

[0045] The acid described in step 1 is 5 mol / L nitric acid;

[0046] The mass ratio of the product II described in step 1 to the volume ratio of the acid is 1 g:100 mL;

[0047] 2. Place 0.2 g of ultrathin carbon nitride nanosheets and 0.01 g of chitosan oligosaccharide in a beaker, add 25 mL of deionized water to obtain a mixture; stir the mixture for 5 h, place it in a polytetrafluoroethylene-lined autoclave, react at 120 ° C for 2 h, cool to room temperature, centrifuge, wash, and then dry at 80 ° C for 24 h to obtain ultrathin carbon nitride nanosheets modified with chitosan oligosaccharide (COS-CN);

[0048] The centrifugation process described in step 2 is: centrifuging at a centrifugal speed of 3000 r / min for 5 minutes, and then removing the supernatant to obtain a solid substance; the washing described in step 2 is: washing with deionized water for 3 times;

[0049] 3. Disperse 0.2 g of chitosan oligosaccharide-modified ultrathin carbon nitride nanosheets in deionized water, then add a metal source, stir for 5 h, place in a polytetrafluoroethylene-lined autoclave, react at 120 ° C for 2 h, cool to room temperature, centrifuge, wash, and then dry at 80 ° C for 24 h to obtain ruthenium oxide cluster-modified ultrathin carbon nitride nanosheets (Ru-COS-CN);

[0050] The metal source described in step 3 is a ruthenium chloride aqueous solution with a concentration of 1 g / L, and the mass ratio of the ruthenium element in the ruthenium chloride to the ultra-thin carbon nitride nanosheet modified with chitosan oligosaccharide is 2:100;

[0051] The volume ratio of the chitosan oligosaccharide-modified ultrathin carbon nitride nanosheets to deionized water in step 3 is 0.2 g:25 mL;

[0052] The centrifugation process described in step three is: centrifuging at a centrifugal speed of 3000 r / min for 5 minutes, then removing the supernatant to obtain a solid substance; the washing described in step three is: washing with deionized water for 3 times.

[0053] Figure 1 Structural characterization of the ultrathin carbon nitride nanosheet modified with ruthenium oxide clusters prepared in Example 1;

[0054] from Figure 1 It can be seen that the material prepared in Example 1 is Ru-COS-CN.

[0055] Figure 2 The morphology and thickness of the ultrathin carbon nitride nanosheet modified with ruthenium oxide clusters prepared in Example 1;

[0056] from Figure 2 It can be seen that the Ru-COS-CN prepared in Example 1 is a two-dimensional ultra-thin layer structure with a thickness of ∼3.0 nm.

[0057] Application Example 1: Application of the ultrathin carbon nitride nanosheet modified with ruthenium oxide clusters prepared in Example 1 in promoting tobacco growth comprises the following steps:

[0058] (1) Tobacco (Nicotiana tabacum L.) seeds from the College of Life Sciences of Heilongjiang University, Heilongjiang Province were sterilized in a sodium hypochlorite solution (5 wt.%) for 20 minutes, and then rinsed with deionized water three times to obtain sterilized seeds;

[0059] (2) placing the sterilized seeds in deionized water and soaking them in a refrigerator at 4°C for 24 hours to obtain expanded tobacco seeds;

[0060] (3) Use plastic pots (12 cm upper edge, 8.5 cm lower edge, 10.5 cm high) as cultivation containers, each pot is filled with 700 g of soil, sow the expanded tobacco seeds in the sterilized soil, and place it in a controlled environment with a relative humidity of 60%, a temperature of 23-24°C, and no light for 24 hours, then place the pots under a plant cultivation lamp with an average light intensity of 14 hours per day and 10 hours at night; after 5-6 days, the tobacco seedlings begin to germinate;

[0061] (4) The metal oxygen cluster modified ultrathin carbon nitride nanosheets (Ru-COS-CN) prepared in Example 1 were added to water, and then ultrasonicated at an ultrasonic power of 100 W for 60 min to obtain an aqueous dispersion of the metal oxygen cluster modified ultrathin carbon nitride nanosheets with a concentration of 100 mg / L; when the tobacco grew to 3-4 true leaves, tobacco seedlings with equivalent growth were selected for foliar spraying, and the foliar spraying was performed once every 5 days with an aqueous dispersion of the metal oxygen cluster modified ultrathin carbon nitride nanosheets with a concentration of 100 mg / L (2 mL per plant per spraying), and the tobacco was harvested on the 20th day after the catalyst was sprayed, and the fresh weight and dry weight were tested.

[0062] Figure 3 To investigate the effect of the ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters prepared in Example 1 on tobacco growth;

[0063] from Figure 3It can be seen that Ru-COS-CN has a significant effect on promoting tobacco growth. Compared with CK (control group), the fresh weight of tobacco treated with Ru-COS-CN ultrathin nanosheets increased by 35.3% and the dry weight increased by 37.6%.

[0064] Application Example 2: The difference between this application example and application example 1 is that the concentration of the aqueous dispersion of ultrathin carbon nitride nanosheets modified by metal oxide clusters in step (4) is adjusted to 0 (CK), 50 mg / L, 100 mg / L or 200 mg / L; the aqueous dispersion of ultrathin carbon nitride nanosheets modified by metal oxide clusters with a concentration of 0 (CK), 50 mg / L, 100 mg / L or 200 mg / L is sprayed on the tobacco leaf surface. The other steps and parameters are the same as those in application example 1.

[0065] Figure 4 The effect of the ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters prepared in Example 1 at different concentrations on tobacco growth in Application Example 2;

[0066] from Figure 4 It can be seen that the ultrathin carbon nitride nanosheets (Ru-COS-CN) modified by ruthenium oxide clusters prepared in Example 1 with different concentrations have a significant effect on promoting tobacco growth. Compared with CK, when the concentration of Ru-COS-CN is 100 mg / L, the effect of promoting tobacco growth is most obvious.

[0067] Example 2: A method for preparing ultrathin boron-doped carbon nitride nanosheets modified with ruthenium oxide clusters (Ru-COS-BCN) is specifically completed by the following steps:

[0068] 1. Preparation of ultra-thin boron-doped carbon nitride nanosheets:

[0069] 35 g of urea was placed in an alumina crucible and transferred to a muffle furnace for calcination, cooled naturally to room temperature, and then ground to obtain product I; product I was mixed with sodium borohydride, ground for a period of time, and then placed in a vacuum tube furnace for calcination, and the product obtained after calcination was washed with water and dried to obtain ultrathin boron-doped carbon nitride nanosheets (BCN);

[0070] The mass ratio of the product I described in step 1 to sodium borohydride is 0.4:0.24;

[0071] In step 1, the product I is mixed with sodium borohydride, ground for 5 minutes, and then placed in a vacuum tube furnace at a temperature of 500° C. for calcination for 2 hours. The calcined product is washed with water three times and then dried at a temperature of 80° C. for 24 hours to obtain ultrathin boron-doped carbon nitride nanosheets (BCN);

[0072] The process of the primary calcination in step 1 is as follows: in air, heating from room temperature to 550°C at a heating rate of 0.5°C / min, and then calcining at 550°C for 3h;

[0073] 2. Place 0.2 g of ultrathin boron-doped carbon nitride nanosheets and 0.01 g of chitosan oligosaccharide in a beaker, add 25 mL of deionized water to obtain a mixture; stir the mixture for 5 h, place it in a polytetrafluoroethylene-lined autoclave, react at 120 ° C for 2 h, cool to room temperature, centrifuge, wash, and then dry at 80 ° C for 24 h to obtain ultrathin boron-doped carbon nitride nanosheets (COS-BCN) modified with chitosan oligosaccharide;

[0074] The centrifugation process described in step 2 is: centrifuging at a centrifugal speed of 3000 r / min for 5 minutes, and then removing the supernatant to obtain a solid substance; the washing described in step 2 is: washing with deionized water for 3 times;

[0075] 3. Disperse 0.2 g of chitosan oligosaccharide-modified ultrathin boron-doped carbon nitride nanosheets in deionized water, then add a metal source, stir for 5 h, and then place in a polytetrafluoroethylene-lined autoclave, react at 120 ° C for 2 h, cool to room temperature, centrifuge, wash, and then dry at 80 ° C for 24 h to obtain ruthenium oxide cluster-modified ultrathin boron-doped carbon nitride nanosheets (Ru-COS-BCN);

[0076] The metal source described in step 3 is a ruthenium chloride aqueous solution with a concentration of 1 g / L, and the mass ratio of the ruthenium element in the ruthenium chloride to the ultra-thin boron-doped carbon nitride nanosheets modified with chitosan oligosaccharide is 2:100;

[0077] The volume ratio of the chitosan oligosaccharide modified ultrathin boron-doped carbon nitride nanosheets to deionized water in step 3 is 0.2 g:25 mL;

[0078] The centrifugation process described in step three is: centrifuging at a centrifugal speed of 3000 r / min for 5 minutes, then removing the supernatant to obtain a solid substance; the washing described in step three is: washing with deionized water for 3 times.

[0079] Application Example 3: The difference between this application example and application example 1 is that: in step (4), the ultrathin boron-doped carbon nitride nanosheets (Ru-COS-BCN) modified by ruthenium oxide clusters prepared in Example 2 are added to water, and then ultrasonicated for 60 minutes at an ultrasonic power of 100 W to obtain an aqueous dispersion of ultrathin boron-doped carbon nitride nanosheets modified by ruthenium oxide clusters with a concentration of 100 mg / L; the aqueous dispersion of ultrathin boron-doped carbon nitride nanosheets modified by ruthenium oxide clusters with a concentration of 100 mg / L is sprayed on the leaf surface of tobacco. The other steps and parameters are the same as those in application example 1.

[0080] Table 1 shows the improvement (percentage) of the growth-promoting effect of the ultrathin boron-doped carbon nitride nanosheets modified with ruthenium oxide clusters prepared in Example 2 on tobacco;

[0081] Table 1

[0082]

[0083] As can be seen from Table 1, Ru-COS-BCN has a significant effect on promoting tobacco growth, and its promoting effect is significantly higher than that of ultrathin carbon nitride nanosheets modified with ruthenium oxide clusters.

[0084] Example 3: The difference between this example and Example 1 is that the metal source described in step three is manganese nitrate with a concentration of 1 g / L, and the mass ratio of the manganese element in manganese nitrate to the ultra-thin carbon nitride nanosheets modified with chitosan oligosaccharides is 2:100; the product obtained in step three is ultra-thin carbon nitride nanosheets modified with manganese oxygen clusters (Mn-COS-CN).

[0085] Figure 5 Structural characterization of the ultrathin carbon nitride nanosheet modified with manganese oxide clusters prepared in Example 3;

[0086] from Figure 5 It can be seen that the material prepared in Example 3 is Mn-COS-CN.

[0087] Application Example 4: The difference between this application example and application example 1 is that: in step (4), the ultra-thin carbon nitride nanosheet (Mn-COS-CN) modified by manganese oxide clusters prepared in Example 3 is added to water, and then ultrasonicated for 60 minutes at an ultrasonic power of 100 W to obtain an aqueous dispersion of ultra-thin carbon nitride nanosheet (Mn-COS-CN) modified by manganese oxide clusters with a concentration of 100 mg / L; the aqueous dispersion of ultra-thin carbon nitride nanosheet (Mn-COS-CN) modified by manganese oxide clusters with a concentration of 100 mg / L is sprayed on the leaf surface of tobacco. The other steps and parameters are the same as those in application example 1.

[0088] Figure 6 The effect of the ultrathin carbon nitride nanosheets modified with manganese oxy-cluster prepared in Example 3 on tobacco growth in Application Example 4;

[0089] from Figure 6 It can be seen that the ultrathin carbon nitride nanosheets modified by manganese oxo clusters (Mn-COS-CN) prepared in Example 3 have a significant promoting effect on tobacco. Compared with CK, the fresh weight of tobacco treated with Mn-COS-CN nanosheets increased by 21.9% and the dry weight increased by 17.8%.

[0090] Application Example 5: Ultrathin carbon nitride nanosheets modified with manganese oxide clusters (Mn-COS-CN) prepared in Example 3

[0091] The application in promoting the growth of sugar beet includes the following steps:

[0092] (1) Sugar beet (7748) seeds from the Agricultural College of Heilongjiang University, Heilongjiang Province, were pelleted seeds from KWS Company, Germany;

[0093] (2) Sow the beet seeds in the fertilized soil and use plastic pots (upper edge 12 cm, lower edge 8.5 cm, height 10.5 cm) as cultivation containers. Each pot is filled with 700 g of substrate soil, compacted evenly, and the seeds are placed in it, and then covered with 200 g of substrate soil. The light radiation intensity in the culture room is 450 μmol / m 2 / s. The average daily light is 14h, the temperature is 25±1℃, the night is 10h, the temperature is 20±1℃, and the relative humidity is 40% to 50%. After 4 to 5 days, the beet seedlings begin to germinate. Before germination, spray the solution of oxadiazine to prevent damping-off disease.

[0094] (3) Starting from the seventh day, the seedlings were screened several times, and by the thirteenth day, two plants were found in each pot. Then, each tray was covered with 100 g of soil.

[0095] (4) The manganese oxide cluster-modified ultrathin carbon nitride nanosheet (Mn-COS-CN) prepared in Example 3 was added to water, and then ultrasonicated at an ultrasonic power of 100 W for 60 min to obtain an aqueous dispersion of the manganese oxide cluster-modified ultrathin carbon nitride nanosheet (Mn-COS-CN) with a concentration of 100 mg / L; when the beet grew to the second pair of true leaves, the leaves were sprayed. The aqueous dispersion of the manganese oxide cluster-modified ultrathin carbon nitride nanosheet (Mn-COS-CN) with a concentration of 100 mg / L was sprayed once every 3 days, and the leaves were sprayed (2.5 mL was sprayed per plant each time).

[0096] Figure 7 To apply the effect of the ultrathin carbon nitride nanosheets modified with manganese oxide clusters prepared in Example 3 on the growth of sugar beet in Example 5;

[0097] from Figure 7 It can be seen that the manganese oxide cluster modified ultrathin carbon nitride nanosheets (Mn-COS-CN) prepared in Example 3 have a significant effect on promoting the growth of sugar beets. Compared with CK, the fresh weight of sugar beets treated with Mn-COS-CN increased by 25.1% and the dry weight increased by 57.8%.

[0098] Comparative Example 1: A method for preparing ultrathin carbon nitride nanosheets, comprising the following steps:

[0099] 35 g of urea was placed in an alumina dry pot and transferred to a muffle furnace, heated to 550°C at a heating rate of 0.5°C / min in air, calcined at 550°C for 3 hours, then naturally cooled to room temperature, and ground to obtain product I; product I was placed in a semi-closed magnetic boat, and then placed in a muffle furnace, heated to 500°C in air at a heating rate of 5°C / min, calcined at 500°C for 2 hours, naturally cooled to room temperature, and ground to obtain product II; a certain amount of product II was placed in a round-bottom flask, refluxed at 120°C for 2 hours using 5 mol / L nitric acid, cooled to room temperature, centrifuged, washed, and dried at 80°C for 24 hours to obtain ultrathin carbon nitride nanosheets (CN).

[0100] Comparative Application Example 1: The difference between this comparative example and Application Example 1 is that in step (4), the ultrathin carbon nitride nanosheets (CN) prepared in the comparative example 1 are added to water, and then ultrasonicated for 60 min at an ultrasonic power of 100 W to obtain an aqueous dispersion of ultrathin carbon nitride nanosheets (CN) with a concentration of 100 mg / L; the aqueous dispersion of ultrathin carbon nitride nanosheets (CN) with a concentration of 100 mg / L is sprayed on the leaf surface of tobacco. The other steps and parameters are the same as those in Application Example 1.

[0101] Comparative Application Example 2: The difference between this comparative example and Application Example 5 is that in step (4), the ultrathin carbon nitride nanosheets (CN) prepared in Comparative Example 1 are added to water, and then ultrasonicated for 60 minutes at an ultrasonic power of 100 W to obtain an aqueous dispersion of ultrathin carbon nitride nanosheets (CN) with a concentration of 100 mg / L; when the beet grows to the second pair of true leaves unfolding, the leaves are sprayed. Spray the ultrathin carbon nitride nanosheets (CN) with an aqueous dispersion with a concentration of 100 mg / L once every 3 days, and spray the leaves. The other steps and parameters are the same as those in Application Example 5.

[0102] Table 2 Improvement of the growth-promoting effect of the ultrathin carbon nitride nanosheets (CN) prepared in Comparative Example 1 on tobacco and sugar beet (percentage);

[0103] Table 2

[0104]

[0105] It can be seen from Table 2 that the ultrathin carbon nitride nanosheets (CN) prepared in Control Example 1 have a significant growth-promoting effect on tobacco and sugar beets, but their promoting effect is significantly lower than that of the ultrathin carbon nitride nanosheets modified with manganese oxide clusters.

[0106] Comparative Example 2: A method for preparing ultrathin boron-doped carbon nitride nanosheets (BCN), comprising the following steps:

[0107] 35g of urea was placed in an alumina dry pot and transferred to a muffle furnace. The temperature was raised to 550°C at a heating rate of 0.5°C / min in air, calcined at 550°C for 3h, then naturally cooled to room temperature and ground to obtain product I; 0.4g of product I was finely ground with 0.24g of sodium borohydride, and then calcined at 500°C at a heating rate of 10°C / min for 2h in a nitrogen atmosphere. After naturally cooling to room temperature, it was washed with deionized water and ethanol. It was dried at 80°C for 12h to obtain ultrathin boron-doped carbon nitride nanosheets (BCN).

[0108] Comparative Application Example 3: The difference between this comparative example and Application Example 1 is that: in step (4), the ultra-thin boron-doped carbon nitride nanosheets (BCN) prepared in Comparative Example 2 are added to water, and then ultrasonicated for 60 minutes at an ultrasonic power of 100 W to obtain an aqueous dispersion of ultra-thin boron-doped carbon nitride nanosheets (BCN) with a concentration of 100 mg / L; the aqueous dispersion of ultra-thin boron-doped carbon nitride nanosheets (BCN) with a concentration of 100 mg / L is sprayed on the leaf surface of tobacco. The other steps and parameters are the same as those in Application Example 1.

[0109] Comparative Application Example 4: The difference between this comparative example and Application Example 5 is that in step (4), the ultra-thin boron-doped carbon nitride nanosheets (BCN) prepared in Comparative Example 2 are added to water, and then ultrasonicated at an ultrasonic power of 100 W for 60 min to obtain an aqueous dispersion of ultra-thin boron-doped carbon nitride nanosheets (BCN) with a concentration of 100 mg / L; when the beet grows to the second pair of true leaves unfolding, foliar spraying is performed. Spray the ultra-thin boron-doped carbon nitride nanosheets (BCN) aqueous dispersion with a concentration of 100 mg / L once every 3 days, and spray the leaves. The other steps and parameters are the same as those in Application Example 5.

[0110] Table 3 Improvement of the growth-promoting effect of the ultrathin boron-doped carbon nitride nanosheets (BCN) prepared in Comparative Example 2 on tobacco and sugar beet (percentage);

[0111] Table 3

[0112]

[0113] It can be seen from Table 3 that BCN has a significant effect on promoting the growth of tobacco and sugar beets, and its promoting effect is higher than that of ultrathin carbon nitride nanosheets, but its promoting effect is significantly lower than that of manganese oxide cluster-modified ultrathin carbon nitride nanosheets, ruthenium oxide cluster-modified ultrathin carbon nitride nanosheets and ruthenium oxide cluster-modified ultrathin boron-doped carbon nitride nanosheets.

[0114] Table 4 Water oxidation activity of ultrathin carbon nitride and ultrathin carbon nitride photocatalysts modified with metal oxygen clusters

[0115]

[0116] In summary, a series of ultrathin carbon nitride and metal oxygen cluster modified ultrathin carbon nitride photocatalysts can promote plant growth, and the plant growth promotion effect is positively correlated with the water oxidation performance of the photocatalyst.

Claims

1. Application of ultrathin carbon nitride nanosheets modified by metal oxygen clusters in promoting plant growth through artificial photosynthesis, characterized in that The metal oxygen cluster-modified ultrathin carbon nitride nanosheet is used to promote plant growth in artificial photosynthesis, which specifically includes the following steps: The metal oxygen cluster modified ultra-thin carbon nitride nanosheets are configured into a water dispersion of a certain concentration, and then the water dispersion of the metal oxygen cluster modified ultra-thin carbon nitride nanosheets is sprayed onto the leaves of the plants; The metal oxide cluster modified ultrathin carbon nitride nanosheets are: manganese oxide cluster modified ultrathin carbon nitride nanosheets, ruthenium oxide cluster modified ultrathin carbon nitride nanosheets, manganese oxide cluster modified ultrathin boron doped carbon nitride nanosheets or ruthenium oxide cluster modified ultrathin boron doped carbon nitride nanosheets.

2. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 1, characterized in that The process of configuring the metal oxygen cluster modified ultrathin carbon nitride nanosheets into a water dispersion of a certain concentration is as follows: adding the metal oxygen cluster modified ultrathin carbon nitride nanosheets into water, and then ultrasonicating for 10 minutes to 60 minutes at an ultrasonic power of 100W to obtain an aqueous dispersion of the metal oxygen cluster modified ultrathin carbon nitride nanosheets; the concentration of the metal oxygen cluster modified ultrathin carbon nitride aqueous dispersion is 50mg / L to 200mg / L.

3. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 1, characterized in that The plant is tobacco, sugar beet, rice, corn or soybean.

4. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 3, characterized in that The plants are cultivated in a soil culture mode.

5. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 1, characterized in that The method for preparing the metal oxide cluster modified ultra-thin carbon nitride nanosheets is specifically completed according to the following steps:

1. Preparation of ultrathin carbon nitride nanosheets and ultrathin boron-doped carbon nitride nanosheets: The urea is placed in an alumina crucible and transferred to a muffle furnace for primary calcination, cooled naturally to room temperature, and then ground to obtain product I; the product I is placed in a semi-enclosed magnetic boat, and then placed in a muffle furnace for secondary calcination, cooled naturally to room temperature, and then ground to obtain product II; the product II is placed in a round-bottom flask, acidified after adding acid, cooled to room temperature, centrifuged, washed with water to neutrality, and dried to obtain ultra-thin carbon nitride nanosheets; the product I is mixed with sodium borohydride, ground for a period of time, and then placed in a vacuum tube furnace for calcination, and the product obtained after calcination is washed with water and dried to obtain ultra-thin boron-doped carbon nitride nanosheets; 2. placing ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets and chitosan oligosaccharide in a beaker, adding a certain amount of deionized water to mix, and obtaining a mixture; after stirring the mixture for several hours, placing it in a polytetrafluoroethylene-lined high-pressure reactor for hydrothermal reaction, cooling it to room temperature, centrifuging, washing, and drying, and obtaining ultrathin carbon nitride nanosheets modified with chitosan oligosaccharide or ultrathin boron-doped carbon nitride nanosheets modified with chitosan oligosaccharide; 3. Disperse the chitosan oligosaccharide-modified ultrathin carbon nitride nanosheets or chitosan oligosaccharide-modified ultrathin boron-doped carbon nitride nanosheets in deionized water, then add a metal source, stir for several hours, and then place in a polytetrafluoroethylene-lined high-pressure reactor for reaction. After cooling to room temperature, centrifuge, wash, and dry to obtain ultrathin carbon nitride nanosheets modified with metal oxygen clusters.

6. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 5, characterized in that The process of the primary calcination described in step one is as follows: in air, heating from room temperature to 400°C to 600°C at a heating rate of 0.1°C / min to 1°C / min, and then calcining at 400°C to 600°C for 2h to 4h; the process of the secondary calcination described in step one is as follows: in air, heating from room temperature to 400°C to 600°C at a heating rate of 5°C / min to 10°C / min, and then calcining at 400°C to 600°C for 2h to 4h; the acid described in step one is 1mol / L to 5mol / L nitric acid; the temperature of the acidification treatment described in step one is 100°C to 120°C, and the time of the acidification treatment is 1h to 3h; the mass ratio of the product II described in step one to the acid is (1g to 2g): (100mL to 200mL).

7. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 5, characterized in that The mass ratio of the product I described in step one to sodium borohydride is (0.2-0.4):(0.1-0.3); in step one, the product I is mixed with sodium borohydride, ground for 2-5 minutes, and then placed in a vacuum tube furnace at a temperature of 450° C. to 550° C. for calcination for 1-3 hours, and the product obtained after calcination is washed with water 3-5 times to obtain ultrathin boron-doped carbon nitride nanosheets.

8. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 5, characterized in that The mass ratio of chitosan oligosaccharide to ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets in the mixture described in step 2 is (1-5):100; the volume ratio of the mass of ultrathin carbon nitride nanosheets or ultrathin boron-doped carbon nitride nanosheets in the mixture described in step 2 to deionized water is (0.2g-0.3g):(20mL-30mL); the stirring time described in step 2 is 5h-8h.

9. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 5, characterized in that The temperature of the hydrothermal reaction described in step 2 is 100°C to 120°C, and the time of the hydrothermal reaction is 2h to 4h; the centrifugation process described in step 2 is: centrifuging at a centrifugal speed of 3000r / min to 4000r / min for 3min to 5min, and then removing the supernatant to obtain a solid substance; the washing described in step 2 is: washing with deionized water for 3 to 5 times; the drying temperature described in step 2 is 60°C to 80°C, and the drying time is 10h to 24h.

10. The use of a metal oxygen cluster modified ultrathin carbon nitride in promoting plant growth by artificial photosynthesis according to claim 5, characterized in that The metal source described in step three is manganese nitrate or ruthenium chloride; the mass ratio of the metal element in the metal source described in step three to the ultrathin carbon nitride nanosheets modified with chitosan oligosaccharide or the ultrathin boron-doped carbon nitride nanosheets modified with chitosan oligosaccharide is (1-3):100; the mass ratio of the ultrathin carbon nitride nanosheets modified with chitosan oligosaccharide or the ultrathin boron-doped carbon nitride nanosheets modified with chitosan oligosaccharide described in step three to deionized water is (0.2g-0.3g):(20mL-30mL); the centrifugation process described in step three is: centrifuging at a centrifugal speed of 3000r / min-4000r / min for 3min-5min, and then removing the supernatant to obtain a solid substance; the washing described in step three is: washing with deionized water for 3-5 times; the drying temperature described in step three is 60°C-80°C, and the drying time is 10h-24h.

Citation Information

Patent Citations

  • Plants having enhanced yield-related traits and producing methods thereof

    CN103890182A

  • Hydrogel seed and preparation method thereof

    CN110999595A

  • Preparation method and application of iron oxyhydroxide modified boron-doped carbon nitride nano-composite photocatalyst

    CN116920911A

  • Photo-catalytic antimicrobial packaging films

    WO2024010829A1